Use of Ni-containing catalysts for synthetic olive mill wastewater steam reforming - Cláudio Rocha (2022)
The olive oil mill wastewater (OMW) is a by-product (with a high organic load) derived from the production of the olive oil. The OMW steam reforming (OMWSR) process was studied herein, aiming to decrease the environmental damage of such effluents; simultaneously, the waste is economically and energetically valorized with the H-2 production. Several Ni-containing catalysts were prepared and tested to compare their performances for the OMWSR using a synthetic OMW effluent; still, stability tests were also carried out. The materials were extensively characterized: thermogravimetric analysis, temperature programmed oxidation/reduction, temperature-programmed desorption of CO2/NH3, chemisorption of H-2, inductively coupled plasma optical emission spectrometry and physical adsorption-desorption of N-2 at-196 & DEG;C. Amongst the materials tested, the Ni-Ru/SiO2 sample stood out, exhibiting high catalytic performance: at 400 & DEG;C, the H-2 yield (> 8 mol(H2)& BULL;mol(OMW)(-1)) and conversion of total organic carbon (asymptotic to 75%) were high during all the 24 h of the long-term test, with only a small deactivation being noticed.